Integration of Manufacturing Information via Dynamic Information Model Aggregation - Schmied, Sebastian; Grossmann, Daniel; Mathias, Selvine G.; Mueller, Ralph Klaus (Vietnam journal of computer science, 2021)
An important part of the industry 4.0 concept is the horizontal and vertical integration of manufacturing systems. Information exchange in traditional production environments happens through interfaces that are connections between strictly defined senders and receivers. This limits the possibility for changing and extending the manufacturing system. A possible approach to enable the information exchange between all system entities uniformly are information models. Such models are semantic descriptions of the available data. The creation of these models needs to follow the manufacturing process, but also requires certain standardization to improve efficiency. Another challenge is the actual technical integration of the information into a common address space. This paper connects an approach for information modeling with a concept for dynamic aggregation. The approach is described with the help of a continuous example that uses OPC UA as a middleware technology.